Pemanfaatan Sistem Informasi Geografik untuk Penentuan Bank Tempat Pembayaran Pajak Bumi dan Bangunan Pelaksana Payment Online System - S Sardana; Rochmad Muryamto (Forum Teknik, 2003)
The research  aims to  do the  spatial  analysis  in selecting  banks for paying  land  and  building tax  (Tp  banps)  which will  be  nominated  as  POS  banlrs  (Payment  Online System)  banks  in Bandung  city  by applying  GIS (Geographic Information  Systems)  technology.GIS spafial  analysis  was  conducted  using  three  coverages;  administrative  boundaries  of Bandung city,  land  use,  and  distibution  of  TP banlcs,  including  their  corresponding attribute data.  verything  technique  and  overlay  operations  using  Arc/Info GIS  software  were  conducted to  select  the  priority of TP banks based  on  some  determined  criteria.Nineteen  Tp banks were  nominated  as POS,  eight of them  were  considered  as the  major priority  where  their  locations  are equally distributed  in Bandung  city.Keywords:  tax,  geographic  information  systems,  spatial  analysis